Economic and Social Drivers of Imported Halal Skincare Purchases Among Urban Generation Z Consumers - Syaefulloh, Syaefulloh; Hamsal, Hamsal (Yayasan Riset dan Pengembangan Intelektual, 2025)
The purpose of this study is to examine the influence of brand image, price, brand trust, attitude, and religiosity on the purchase decision of imported halal skincare products. This research employs descriptive analysis and Structural Equation Modeling (SEM). Data were collected through questionnaires filled out by Generation Z consumers of imported halal skincare products in Pekanbaru city, with a sample size of 96 respondents determined using the Lemeshow formula. The results show that brand image has a positive and significant effect on behavioral intention. Price has a positive but not significant effect on behavioral intention. Brand trust has a positive and significant effect on behavioral intention. Attitude and religiosity have no significant effect on behavioral intention. Behavioral intention has a positive and significant effect on use behavior.